METHYL RED ADSORPTION BY BIODEGRADABLE POLYCAPROLACTONE/RICE HUSK ASH/TiO2 NANOFILLER HYBRID BIONANOCOMPOSITES: SYNTHESIS AND CHARACTERIZATION - Armelia Yuniani; Erna Frida; Syahrul Humaidi (RADJA PUBLIKA, 2025)
The contamination of wastewater by synthetic dyes such as Methyl Red poses serious environmental and health risks, necessitating effective remediation methods. This study investigates the synthesis and characterization of hybrid bionanocomposites composed of polycaprolactone (PCL), rice husk ash (RHA), and titanium dioxide (TiO2) nanoparticles for the efficient degradation of Methyl Red (MR) dye. The composites were prepared using a co-precipitation method for the incorporation of nano-RHA and TiO2. Characterization of the bionanocomposites was conducted through scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and photodegradation tests. XRD analysis, using the Scherrer equation, revealed crystallite sizes ranging from 19.01 nm (composite S0) to 27.25 nm (composite S2). FTIR spectra showed characteristic absorption peaks corresponding to Ti–O (669.29 cm⁻¹), Si–O (970.19 cm⁻¹), and C–H (2960.73 cm⁻¹) bonds. The photodegradation results indicated a significant improvement in dye adsorption, with the highest degradation efficiency observed in composite S1, achieving 93.55% degradation after 45 hours of UV irradiation. The degradation efficiencies of S0, S1, and S2 were found to be 87.1%, 93.55%, and 25.81%, respectively, under the same conditions. The incorporation of TiO2 and RHA in PCL significantly enhanced its photocatalytic activity. This study demonstrates the potential of these bionanocomposites as sustainable materials for textile wastewater treatment